Nanometals for Solar‐to‐Chemical Energy Conversion: From Semiconductor‐Based Photocatalysis to Plasmon‐Mediated Photocatalysis and Photo‐Thermocatalysis. Issue 32 (17th May 2016) - Meng, Xianguang; Liu, Lequan; Ouyang, Shuxin; Xu, Hua; Wang, Defa; Zhao, Naiqin; Ye, Jinhua
Abstract : Nanometal materials play very important roles in solar‐to‐chemical energy conversion due to their unique catalytic and optical characteristics. They have found wide applications from semiconductor photocatalysis to rapidly growing surface plasmon‐mediated heterogeneous catalysis. The recent research achievements of nanometals are reviewed here, with regard to applications in semiconductor photocatalysis, plasmonic photocatalysis, and plasmonic photo‐thermocatalysis. As the first important topic discussed here, the latest progress in the design of nanometal cocatalysts and their applications in semiconductor photocatalysis are introduced. Then, plasmonic photocatalysis and plasmonic photo‐thermocatalysis are discussed. A better understanding of electron‐driven and temperature‐driven catalytic behaviors over plasmonic nanometals is helpful to bridge the present gap between the communities of photocatalysis and conventional catalysis controlled by temperature. The objective here is to provide instructive information on how to take the advantages of the unique functions of nanometals in different types of catalytic processes to improve the efficiency of solar‐energy utilization for more practical artificial photosynthesis. Abstract : Nanometal materials play very important roles in solar‐to‐chemical energy conversion due to their unique catalytic and optical characteristics. Recent research achievements of nanometals regarding applications in semiconductor photocatalysis, plasmonic photocatalysis, and plasmonic photo‐thermocatalysis are presented. Instructive information on how to take the advantage of nanometals in these catalytic processes for efficient artificial photosynthesis is provided.